2001
DOI: 10.1097/00006676-200108000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Insulin–Leptin–Visceral Fat Relation During Weight Loss

Abstract: In this study, we found that leptin and insulin were related in weight loss. The data suggest that insulin may act as a strong regulator of leptin secretion during weight loss and that circulating leptin levels can be predicted by insulin level. Using sibutramine in conjunction with hypocaloric diet reduced body weight and decreased fat mass significantly. Visceral and subcutaneous abdominal fat depots were shown to decrease. Whether sibutramine exerts any selective reduction of visceral abdominal fat as oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
1
11
1
1
Order By: Relevance
“…In a recent meta-analysis, modest weight reduction has also been shown to improve glucose intolerance [33]. Similarly, sibutramine treatment is associated with significant improvement in the insulin sensitivity indexes [14][15][16][17][18][19]. In the present study, we also detected a significant improvement in the HOMA-IR index after 3 and 12 months of sibutramine treatment.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In a recent meta-analysis, modest weight reduction has also been shown to improve glucose intolerance [33]. Similarly, sibutramine treatment is associated with significant improvement in the insulin sensitivity indexes [14][15][16][17][18][19]. In the present study, we also detected a significant improvement in the HOMA-IR index after 3 and 12 months of sibutramine treatment.…”
Section: Discussionsupporting
confidence: 80%
“…In recent literature, sibutramine has enabled a 7% reduction in initial weight after 1 year of therapy [11][12][13]. Generally, sibutramine treatment is associated with significant improvement in the insulin sensitivity, serum leptin and hsCRP [14][15][16][17][18][19]. On the other hand, it has also been demonstrated that metformin, an antihyperglycemic agent, decreases hyperinsulinemia and the insulin resistance leading to decreased adiposity in obese and noninsulin-dependent diabetes mellitus [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…6,71 Increasing evidence of the biological role of VAT adds greatly to the strength of the conclusion that %dV/%dS is greatest during rapid weight loss with VLCDs or modest weight loss. Many studies have shown preferential improvement in hormonal and metabolic function occurs soon after modest weight loss and/or exercise, 60,72 indicating a tight association of obesity comorbidity on neutral or positive energy balance. Perhaps early preferential loss of visceral fat is physiological, driven by an immediate need for energy, in the face of acute negative energy intake, from a metabolically active fat store uniquely situated up stream from the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss through diet alone or diet and exercise interventions results in elevations [29][30][31][32][33][34][35][36][37][38][39] or no change [35,40] in adiponectin levels and reductions in leptin levels [29][30][31][32][33][34][35][36][37][38][39] in obese healthy individuals. On the other hand, only one study to date has examined resistin levels after weight loss [41].…”
Section: Introductionmentioning
confidence: 99%